Enhancing Oxygen Reduction Activity and Cr Tolerance of Solid Oxide Fuel Cell Cathodes by a Multiphase Catalyst Coating. (10th March 2021) - Niu, Yinghua; Zhou, Yucun; Lv, Weiqiang; Chen, Yu; Zhang, Yanxiang; Zhang, Weilin; Luo, Zheyu; Kane, Nicholas; Ding, Yong; Soule, Luke; Liu, Yuchen; He, Weidong; et al.
Abstract: Intermediate temperature solid oxide fuel cells (IT‐SOFCs) are cost‐effective and efficient energy conversion systems. The sluggish oxygen reduction reaction (ORR) and the degradation of cathodes are critical challenges to the commercialization of IT‐SOFCs. Here, a highly efficient multiphase (MP) catalyst coating, consisting of Ba1 −x Co0.7 Fe0.2 Nb0.1 O3− δ (BCFN) and BaCO3, to enhance the ORR activity and durability of the state‐of‐the‐art lanthanum strontium cobalt ferrite (La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ, LSCF) cathode is reported. The conformal MP catalyst‐coated LSCF cathode shows a polarization resistance ( R p ) of 0.048 Ω cm 2 at 650 °C, about one order of magnitude smaller than that of the bare LSCF. In an accelerated Cr‐poisoning test, the degradation rate of the catalyst‐coated LSCF electrode is 10 −3  Ω cm 2  h −1 (0.59% h −1 ) over 200 h, only one fifth of the degradation rate of the bare LSCF electrode at 750 °C. In addition, anode‐supported single cells with the MP catalyst‐coated LSCF cathode show a dramatically enhanced peak power density (1.4 W cm −2  vs 0.67 W cm −2 at 750 °C) and increased durability against Cr and H2 O. Both experimental results and density functional theory‐based calculations indicate that the BCFN phase improves the ORR activity while the BaCO3 phase enhances the stability of the LSCF cathode. Abstract : A multiphase catalyst (Ba1 −x Co0.7 Fe0.2 Nb0.1 O3− δ (BCFN)‐BaCO3 )‐coated lanthanum strontium cobalt ferrite cathode is developed for intermediate temperature solid oxide fuel cells, demonstrating exceptional oxygen reduction reaction (ORR) activity and excellent stability against H2 O and Cr. The excellent performance is attributed to the improved ORR activity of the BCFN phase and the enhanced contaminants tolerance of the BaCO3 phase.